Santa Rosa (Schooner) records - Santa Rosa (Schooner)
List and commendation relating to Francisco de Fuentes and the crew of the Spanish schooner Santa Rosa.
Collection material in Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fuentes, Francisco de; Ship's papers -- 19th century